Contrasting state-run tv channel ratings: a comparative analysis of the evolution of “Qazaqstan” and “Al-Jazeera” - Utemissov, Zhanibek (Penerbit Universiti Kebangsaan Malaysia, 2023)
A comparative analysis of the activities of pro-state TV channels Qazaqstan TV and Al-Jazeera and their relationship with the state are detailed herein, taking into account the specifics of their functioning and the evolution of the television industry in Kazakhstan and Qatar. Using the example of Al-Jazeera, the study demonstrates that the state funding of media does not necessarily aim to fuel branding propaganda through TV channels, but rather to help them acquire independence from state regulation, for example, increasing the role of an entity that complements the functions of the state, and identifies the information needs of its audience. On the other hand, data are presented that indicate the difficulties Qazaqstan will have to face in the post-pandemic era and the rapidly changing digital world, as well as challenges ahead in terms of competitiveness and competition for the audience. Qualitative and quantitative statistical methods were employed to validate the hypothesis that the rating of networks does not hang with the factor of state funding, but related to the content materials. A detailed content analysis of the information agenda was carried out, and a brief historical development of both TV channels was studied. Statistical data provided by open international sources, as well as comparative financial data on these channels, were investigated. In the context of the article, recommendations are made for Qazaqstan TV to tailor their agenda according to a changing socio-political environment.